2017
DOI: 10.3390/nano7060126
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Manganese Dioxide Coatings on High Aspect Ratio Micro-Pillar Arrays for 3D Thin Film Lithium Ion Batteries

Abstract: In this work, we present the electrochemical deposition of manganese dioxide (MnO2) thin films on carbon-coated TiN/Si micro-pillars. The carbon buffer layer, grown by plasma enhanced chemical vapor deposition (PECVD), is used as a protective coating for the underlying TiN current collector from oxidation, during the film deposition, while improving the electrical conductivity of the stack. A conformal electrolytic MnO2 (EMD) coating is successfully achieved on high aspect ratio C/TiN/Si pillar arrays by tailo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…[47,48] The MnO2 films are deposited by electrochemical deposition (ECD) where excellent conformality is obtained due to the resistive nature of the MnO2. [36,49] Alternatively, conformal MnO2 (and MnO) films can also be obtained by ALD. [50] Using 3D ECD MnO2 films converted to LiMn2O4, already a footprint capacity of 500 µAh cm -2 is shown for a 350 nm thin film.…”
Section: Cathodesmentioning
confidence: 99%
“…[47,48] The MnO2 films are deposited by electrochemical deposition (ECD) where excellent conformality is obtained due to the resistive nature of the MnO2. [36,49] Alternatively, conformal MnO2 (and MnO) films can also be obtained by ALD. [50] Using 3D ECD MnO2 films converted to LiMn2O4, already a footprint capacity of 500 µAh cm -2 is shown for a 350 nm thin film.…”
Section: Cathodesmentioning
confidence: 99%
“…Concerning the electron transfer between the semiconductive MnO 2 and the current collector, a few studies have reported on the poor adhesion and mechanical stability of MnO 2 on conductive substrates of various chemical composition and roughness. , Furthermore, because of the moderate electronic conductivity (10 –3 –10 –4 S·cm –1 ) of MnO 2 , , the ohmic drop is expected to rise together with the film thickness. All these issues can potentially be solved by using a 3D nanostructured current collector, with a high aspect ratio, well-suited for the conformal electrodeposition of thin films of MnO 2 to provide shorter ion diffusion distances and better electron harvesting paths. , Previously, such a strategy has been successfully exploited to improve the performances of MnO 2 -based supercapacitors as well as MnO 2 cathodes toward reversible Li + insertion in organic electrolytes …”
Section: Introductionmentioning
confidence: 99%
“…Similar deposition was also achieved with C-coated Si pillars as demonstrated in our earlier work. 26 Ability to conformally coat high-aspect ratio structures opens up a variety of new applications of EMD material, including Li-ion batteries with increased battery capacity due to surface microstructuring.…”
Section: Porosit Y = 100% · (1 − R B S F Ilm Thickness/s E M F Ilm Thmentioning
confidence: 99%